Inhibitory Effects of Green Tea and (-)-Epigallocatechin Gallate on Transport by OATP1B1, OATP1B3, OCT1, OCT2, MATE1, MATE2-K and P-Glycoprotein - Knop, Jana; Misaka, Shingen; Singer, Katrin; Hoier, Eva; Müller, Fabian; Gläser, Hartmut; König, Jörg; Fromm, Martin (PLoS ONE, 2015)
Green tea catechins inhibit the function of organic anion transporting polypeptides (OATPs) that mediate the uptake of a diverse group of drugs and endogenous compounds into cells. The present study was aimed at investigating the effect of green tea and its most abundant catechin epigallocatechin gallate (EGCG) on the transport activity of several drug transporters expressed in enterocytes, hepatocytes and renal proximal tubular cells such as OATPs, organic cation transporters (OCTs), multidrug and toxin extrusion proteins (MATEs), and P-glycoprotein (P-gp). Uptake of the typical substrates metformin for OCTs and MATEs and bromosulphophthalein (BSP) and atorvastatin for OATPs was measured in the absence and presence of a commercially available green tea and EGCG. Transcellular transport of digoxin, a typical substrate of P-gp, was measured over 4 hours in the absence and presence of green tea or EGCG in Caco-2 cell monolayers. OCT1-, OCT2-, MATE1- and MATE2-K-mediated metformin uptake was significantly reduced in the presence of green tea and EGCG (P < 0.05). BSP net uptake by OATP1B1 and OATP1B3 was inhibited by green tea [IC50 2.6% (v/v) and 0.39% (v/v), respectively]. Green tea also inhibited OATP1B1- and OATP1B3-mediated atorvastatin net uptake with IC50 values of 1.9% (v/v) and 1.0% (v/v), respectively. Basolateral to apical transport of digoxin was significantly decreased in the presence of green tea and EGCG. These findings indicate that green tea and EGCG inhibit multiple drug transporters in vitro. Further studies are necessary to investigate the effects of green tea on prototoypical substrates of these transporters in humans, in particular on substrates of hepatic uptake transporters (e.g. statins) as well as on P-glycoprotein substrates.
EVALuna2:8693

The Nonmetabolized β-Blocker Nadolol Is a Substrate of OCT1, OCT2, MATE1, MATE2-K, and P-Glycoprotein, but Not of OATP1B1 and OATP1B3 - Misaka, Shingen; Knop, Jana; Singer, Katrin; Hoier, Eva; Keiser, Markus; Müller, Fabian; Gläser, Hartmut; König, Jörg; Fromm, Martin (Molecular Pharmaceutics, 2016)
Nadolol is a nonmetabolized ?-adrenoceptor antagonist and is a substrate of OATP1A2, but not of OATP2B1. However, other drug transporters involved in translocation of nadolol have not been characterized in detail. We therefore investigated nadolol as a potential substrate of the hepatic uptake transporters OATP1B1, OATP1B3, and OCT1 and of the renal transporters OCT2, MATE1, and MATE2-K expressed in HEK cells. Moreover, the importance of P-glycoprotein (P-gp) for nadolol transport was studied using double transfected MDCK-OCT1-P-gp cells. Nadolol was not transported by OATP1B1 and OATP1B3. In contrast, a significantly higher nadolol accumulation (at 1 and 10 ?M) was found in OCT1, OCT2, MATE1, and MATE2-K cells compared to control cells (P < 0.01). Km values for OCT2-, MATE1-, and MATE2-K-mediated nadolol uptake were 122, 531, and 372 ?M, respectively. Cimetidine (100 ?M, P < 0.01) and trimethoprim (100 ?M, P < 0.001) significantly inhibited OCT1-, OCT2-, MATE1-, and MATE2-K-mediated nadolol transport. The P-gp inhibitor zosuquidar significantly reduced basal to apical nadolol transport in monolayers of MDCK-OCT1-P-gp cells. In summary, nadolol is a substrate of the cation transporters OCT1, OCT2, MATE1, MATE2-K, and of P-gp. These data will aid future in vivo studies on potential transporter-mediated drug-drug or drug-food interactions with involvement of nadolol.
EVALuna2:8690